A COLLABORATIVE SHARING OF STORIES ON A JOURNEY TOWARD RECONCILIATION: “BELONGING TO THIS PLACE AND TIME” - Keliipio, Kauʻi; Perry, Kimberly; Elderton, Colleen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
This paper emerges from the particular field experiences of three “settler” colleagues working in a teacher education program, each of whom found that their personal and professional relationships with First Nations, Metís, and Inuit people had a positive and constructive bearing on how they responded to provincial mandates and the Truth and Reconciliation Commission’s Calls to Action. PARTAGE COLLABORATIF DE RECITS DANS LE CADRE D’UN CHEMINEMENT VERS LA RECONCILIATION : « APPARTENIR A CE TERRITOIRE ET CETTE EPOQUE » Cet article a vu le jour suite à l’expérience vécue au sein d’un stage par trois collègues « colonisateurs » oeuvrant dans un programme de formation des enseignants. Ceux-ci ont constaté que leur relation personnelle et professionnelle avec les Premières Nations, les Métis et les Inuits avaient eu une incidence positive et utile sur leur manière de répondre aux mandats provinciaux et aux appels à l’action formulés dans le cadre de la Commission de vérité et réconciliation.